Stand and give the password : I have served my country : pass, friend, your future is assured - Queensland. State Recruiting Committee of Queensland ([Brisbane?] : issued by the Q'land Recruiting Committee, 1914)
World War I Queensland recruiting notice. "I have served my country" appears in red, with the remaining text in black. A "Q" with the initials "G.P." inside it appears below left of the main text.
Caption title.
Also available online
Keywords: Australia -- Armed Forces -- Recruiting, enlistment, etc. -- World War, 1914-1918 -- Posters; Queensland. -- State Recruiting Committee of Queensland -- Posters; Recruiting and enlistment -- Posters; World War, 1914-1918 -- Participation, Australian -- Posters; Broadsides -- Australia; War posters -- Australia; Australian